U.S. and Finnish high school science engagement during the COVID‐19 pandemic. (1st August 2021) - Maestrales, Sarah; Marias Dezendorf, Rachel; Tang, Xin; Salmela‐Aro, Katariina; Bartz, Kayla; Juuti, Kalle; Lavonen, Jari; Krajcik, Joseph; Schneider, Barbara
Abstract : When the COVID‐19 pandemic struck, research teams in the United States and Finland were collaborating on a study to improve adolescent academic engagement in chemistry and physics and the impact remote teaching on academic, social, and emotional learning. The ongoing "Crafting Engaging Science Environments" (CESE) intervention afforded a rare data collection opportunity. In the United States, students were surveyed at the beginning of the school year and again in May, providing information for the same 751 students from before and during the pandemic. In Finland, 203 students were surveyed during remote learning. Findings from both countries during this period of remote learning revealed that students' academic engagement was positively correlated with participation in hands‐on, project‐based lessons. In Finland, results showed that situational engagement occurred in only 4.7% of sampled cases. In the United States, students show that academic engagement, primarily the aspect of challenge, was enhanced during remote learning. Engagement was in turn correlated with positive socioemotional constructs related to science learning. The study's findings emphasise the importance of finding ways to ensure equitable opportunities for students to participate in project‐based activities when learning remotely.